Empirical Study On Impact Of Demographic And Economic Changes On Pension Costs - Shaira Binti Yusof
Over the last century, general population mortality has improved significantly and on a global basis. This mortality improvements discussed widely in most countries was the mortality of elderly. Malaysia population also has experienced this phenomenon. The continuing decline of mortality has resulted in the aging of population and the numbers of elderly persons have increased substantially. As this trend appears likely to continue at least over the near term, mortality improvements are expected to continue to impact the viability of national social programs worldwide as well as the financial stability of insurance programs including pension plans and annuities. Besides that, a continuation of the same financial standard of living after retirement as before is very importance to retired person. The pension provider has a responsibility to ensure their employees receive the sufficient benefit after retirement and regularly monitor the factors that cause insufficient funds to pay benefit to retirees. This study estimated mortality rates for government pensioners using data from Jabatan Perkhidmatan Awam (JPA) for a period of 30 years (1980-2009) using Visual Basic Application (VBA) for age 55 and above. This study found a decreasing trend in mortality rates for both genders. Also, it was found that mortality rates among males are high compared to females for all ages and mortality for both genders are lower compared to mortality for actual Malaysian Population. Then, mortality rates will be predicted using simple mortality model. The results obtained will be used to see the impact on pension costs for the future. In order to calculate pension costs, Accrued Benefit Cost Method and Projected Benefit Cost Method will be used in this study. The other two modifications of the Accrued Benefit Cost Method and Projected Benefit Cost Method will be considered in this study are constant amount (CA), which is known as a CA modification and constant percentage of salary (CS), known as a CS modification. In this study, a comparison between these two methods will be investigated in terms of pension costs. This study attempts to examine the impact of mortality improvements and the changes in interest rates on pension costs. The mortality assumptions and the implied mortality experience of the plan can potentially have a significant impact on costs, it has a directly related to pension cost. While for interest rate assumptions, it is inversely related to the pension costs.